Extraction and characterization of inulin from Taro Beneng (Xanthosoma undipes K. Koch) - Eris, F.R.; Pamela, V.Y.; Kusumasari, S.; Meindrawan, B.; Sari, A.K (Penerbit Universiti Kebangsaan Malaysia, 2025)
Inulin acts as a low-calorie dietary fiber and as a prebiotic that can stimulate the growth of probiotic bacteria in the intestines of humans. The development on the production of inulin continues to be carried out through research. This study aimed to determine the optimal acetone concentration and precipitation time for extracting high-purity inulin from Beneng taro (Xanthosoma undipes K. Koch) and to evaluate the physicochemical characteristics of the extract. A factorial randomized block design was applied with three acetone concentrations (20%, 45%, and 70%) and three precipitation times (12, 18, and 24 h). The extraction yield, water content, whiteness degree, solubility, inulin content, and functional groups (FTIR) were analyzed. The results showed that acetone concentration and precipitation time significantly affected yield, water content, and solubility (p < 0.05), while their interaction significantly influenced inulin content. The highest average yield (10.30%) was obtained with 70% acetone, the lowest average water content (4.97%) with 70% acetone, and the highest average solubility (34.58%) with a 24 h precipitation time. The greatest inulin content (53.05%) resulted from the combination of 20% acetone with 12 h precipitation, showing 97.20% spectral similarity to commercial inulin. The optimal extraction condition was 20% acetone for 12 h, producing inulin with high purity, moderate yield (9.16%), and favorable physicochemical properties. These findings demonstrate Beneng taro’s potential as a local inulin source for functional food applications